Theories, models and frameworks in men’s health studies: A scoping review - Khalid Ashraf; Chirk Jenn Ng; Kim Leng Goh (Journal of Men's Health, 2021)
Background and Objectives: Men’s health has been acknowledged as a broad field that comprises not only of male specific diseases, but involves widely differing disciplines. While a significant number of studies have looked into the definition of men’s health, there is a lack of concerted attempts to collectively review the theories, models and frameworks in men’s health studies. This paper presents an overview of theories, models and frameworks used in past men’s health studies. Material and Methods: A scoping review was conducted using the Arksey and O’Malley framework. Publications were searched in three electronic databases. Two independent researchers performed publications’ selection and data charting. Any disagreement was resolved by consultation with a third researcher. Results: One hundred and forty publications were included in this review. Within these publications, 87 theories, models and frameworks were identified. They were found to be generic to either health sciences or social sciences, or specific to men’s health. Three type of processes were observed among the theories, models and frameworks, namely, behavioural, cognitive and gender processes. The findings also indicated a lack of publications about theories, models and frameworks in men’s health studies from developing countries and outside the western world. Conclusion: The results revealed the multidisciplinary nature of men’s health. However, due to the fragmentation of theoretical understanding by separate disciplines, an interdisciplinary approach is necessary for this field.